Penerapan Model Pembelajaran Team Quizz Terhadap Hasil Belajar IPS - Pika Pika; Yeni Asmara; Dedy Firduansyah (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
The purpose of the study was to find out to determine the increase in social studies learning outcomes for grade IV Taba Tengah State Elementary School after the application of the Team Quizz learning model. The research design was in the form of a quasi-experimental category of pre-test and post -test group. The research was conducted at the Taba Tengah State Elementary School with the population being fourth grade students at the Taba Tengah State Elementary School. Sampling was carried out with a saturated sample so that the sample taken was the sampling of the study was carried out by saturated sampling of fourth grade elementary school students at Taba Tengah State Elementary School. Teknol data collection was carried out by a test technique consisting of 25 questions. The collected data was the analyzed using the Z-tes. Based on the results of the research and discussion, it can be coneluded that the social studies learning outcomes in grade IV SD Negeri Taba Tengah increased by 84.61%. Meanwhile, based on the results of the analysis of hypothesis testing, it was obtained that Zcount (8,011)>Ztabel (1,708) thus the proposed hypothesis was acceptes as true, social studies learning outcomes in grade IV SD Negeri Taba Tengah increased after the implementation of the Team Quizz learning model. Keywords: application, learning outcomexs, Team Quizz.